Exposure Therapy and Simultaneous Repetitive Transcranial Magnetic Stimulation: A Controlled Pilot Trial for the Treatment of Posttraumatic Stress Disorder. Issue 1 (March 2019) - Fryml, Leah D.; Pelic, Christopher G.; Acierno, Ron; Tuerk, Peter; Yoder, Matthew; Borckardt, Jeffrey J.; Juneja, Natasha; Schmidt, Matthew; Beaver, Kathryn L.; George, Mark S.
Abstract : Objectives: This is a small preliminary but novel study assessing the feasibility of repetitive transcranial magnetic stimulation (rTMS) delivery to veterans with posttraumatic stress disorder (PTSD) while they simultaneously receive prolonged exposure (PE) therapy. Methods: A prospective, randomized, double-blinded, active sham-controlled design combined weekly sessions of rTMS and standard PE at the Veterans Administration Hospital. Eight adult patients received a full course of protocol-driven PE therapy and were randomly assigned to receive either rTMS or sham rTMS. Repetitive transcranial magnetic stimulation was delivered to the right or left prefrontal cortex with a figure-eight solid core coil at 120% motor threshold, 10 Hz, 5-second train duration, and 10-second intertrain interval for 30 minutes (6000 pulses) weekly for 5 weeks (30, 000 stimuli). Results: Of the 12 veterans consented, 8 completed the study treatment protocol. The dropout rate was 34%, roughly equivalent to the pooled average dropout rates observed in traditional PE therapy with Operation Enduring Freedom/Operation Iraqi Freedom veterans with PTSD, suggesting that veterans had no difficulty tolerating the addition of rTMS to PE therapy and that this is a feasible study design for larger trials in the future. Clinician-Administered PTSD Symptom scores reflected a general nonsignificant trend toward improvement, and subjects with comorbid major depression appeared to experience significant antidepressant benefit with treatment despite the fact that the doses used in this protocol were much smaller than those used to treat patients with major depressive disorder. Conclusions: This pilot study demonstrates the safety and feasibility of rTMS delivery to PTSD patients while they simultaneously receive PE. This unique approach to the treatment of PTSD highlights the need for further studies with larger sample sizes to assess treatment outcomes.